Enhancement of lycopene bioaccessibility in tomatoes using excipient emulsions: Effect of dark tea polysaccharides. (January 2023) - Wang, Chao; Fu, Yinxin; Cao, Yi; Huang, Jialu; Lin, Hongyi; Shen, Peiyi; Julian McClements, David; Han, Lingyu; Zhao, Tiantian; Yan, Xiaoxuan; Li, Qian
Graphical abstract: Highlights: A novel excipient emulsion was fabricated by adding dark tea polysaccharides. Tea polysaccharides improved the physical stability of excipient emulsion. Tea polysaccharides enhanced the antioxidant activity of excipient emulsion. Tea polysaccharides increased the bioaccessibility of lycopene in tomatoes. Abstract: This study fabricated a novel excipient emulsion by adding dark tea polysaccharides to improve the bioaccessibility of lycopene from tomatoes. Results indicated that addition of tea polysaccharides greatly increased the antioxidant activity of excipient emulsions. Additionally, tea polysaccharides markedly improved the physical stability of excipient emulsion when being mixed with tomato puree and passing through a simulated gastrointestinal tract, contributing to an increase in electrostatic and steric repulsion between the droplets. Besides, certain amount of tea polysaccharides (0.05 – 0.2 wt%) could increase the rate and extent of lipid digestion in tomato-emulsion mixtures. Finally, lycopene bioaccessibility was significantly increased (from 16.95 % to 26.21 %) when 0.1 wt% tea polysaccharides were included, which was mainly ascribed to the ability of tea polysaccharides to increase lipid digestion and reduce carotenoid oxidation within the gastrointestinal tract. These results suggest that well-designed excipient emulsions may increase carotenoids bioavailability in the complex food matrices.